Business Modeling and Software Design First International Symposium, BMSD 2011, Sofia, Bulgaria, July 27-28, 2011, Revised Selected Papers - Shishkov, Boris; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book contains the extended and revised versions of eight of the ten full papers (out of 58 submissions) presented at the First International Symposium on Business Modeling and Software Design (BMSD 2011), held in Sofia, Bulgaria. The theme of BMSD 2011 was "Business Models and Advanced Software Systems," and the related scientific areas of interest were: business models and requirements, business models and services, business models and software, and information systems architecture.
Keywords: Economics; Software engineering; Information systems; Management information systems; Economics/Management Science; Business Information Systems; Information Systems Applications (incl. Internet).; Computer Appl. in Administrative Data Processing; Software Engineering